PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS MERANGIN - Bransika, Dien Muhammad Ismal; Iswantir, Iswantir; Wati, Salmi; Husni, Arman; Zakir, Supratman (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
Islamic Religious Education (PAI) in Public Universities (PTU) has a strategic role in shaping the character of students who are moderate, religious, and moral. However, in practice, the implementation of PAI still faces various challenges that cause discrepancies between the ideal curriculum and factual implementation in the field. This study aims to examine the curriculum structure, integration of religious moderation values, challenges in developing teaching materials, and the perceptions of lecturers and students regarding the effectiveness of PAI learning at Merangin University. The method used is a qualitative approach with case studies, through observation, in-depth interviews, and documentation. The results of the study show that although the curriculum has referred to PMA No. 33 of 2021, its implementation is still textual, rigid, and has minimal contextualization. The learning method is dominated by lectures, teaching materials tend to be normative, and have not been effectively integrated with other disciplines. The Islamization of knowledge and the value of moderation have not been fully internalized in the learning process. Lecturers face pedagogical limitations, and students lack critical and creative space. This study recommends strengthening lecturer competencies, developing contextual teaching materials, and integrating Islamic values ??with contemporary science as strategies for renewing Islamic Religious Education at PTU. ABSTRAKPendidikan Agama Islam (PAI) di Perguruan Tinggi Umum (PTU) memiliki peran strategis dalam membentuk karakter mahasiswa yang moderat, religius, dan berakhlak. Namun dalam praktiknya, pelaksanaan PAI masih menghadapi berbagai tantangan yang menyebabkan terjadinya diskrepansi antara kurikulum ideal dan implementasi faktual di lapangan. Penelitian ini bertujuan untuk mengkaji struktur kurikulum, integrasi nilai-nilai moderasi beragama, tantangan pengembangan bahan ajar, serta persepsi dosen dan mahasiswa terhadap efektivitas pembelajaran PAI di Universitas Merangin. Metode yang digunakan adalah pendekatan kualitatif dengan studi kasus, melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa meskipun kurikulum telah merujuk pada PMA No. 33 Tahun 2021, implementasinya masih bersifat tekstual, kaku, dan minim kontekstualisasi. Metode pembelajaran didominasi ceramah, bahan ajar cenderung normatif, serta belum terintegrasi dengan disiplin ilmu lain secara efektif. Islamisasi pengetahuan dan nilai moderasi belum diinternalisasi secara utuh dalam proses pembelajaran. Dosen menghadapi keterbatasan pedagogik, dan mahasiswa kurang mendapat ruang kritis dan kreatif. Penelitian ini merekomendasikan penguatan kompetensi dosen, pengembangan bahan ajar kontekstual, serta integrasi nilai keislaman dengan keilmuan kontemporer sebagai strategi pembaruan PAI di PTU.